2008
DOI: 10.1016/j.freeradbiomed.2008.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of electrostatics in redox modulation of oxidative stress by Mn porphyrins: Protection of SOD-deficient Escherichia coli via alternative mechanism where Mn porphyrin acts as a Mn carrier

Abstract: Understanding the factors that determine the ability of Mn porphyrins to scavenge reactive species is essential for tuning their in vivo efficacy. We present herein the revised structure-activity relationships accounting for the critical importance of electrostatics in the Mn porphyrin-based redox modulation systems and show that the design of effective SOD mimics (per se) based on anionic porphyrins is greatly hindered by inappropriate electrostatics. A new strategy for the beta-octabromination of the prototy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
84
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(88 citation statements)
references
References 58 publications
3
84
1
Order By: Relevance
“…Further, along with our mechanistic studies we observed a dramatic impact of the positive charges of the Mn porphyrin on the O 2 •− dismutation; the rate constants are more than two orders of magnitude higher when compared to the neutral or negatively charged porphyrins [3,4]. Thus, Mn III TE-2-PyP 5+ is 130-fold more potent SOD mimic than its singly charged Mn III Br 8 T-2-PyP + [3], and 400-fold more potent than its negatively charged analogue [Mn III Br 8 TSPP] 3− [4]. Charge distribution had also remarkable impact [2].…”
Section: Introductionsupporting
confidence: 61%
See 4 more Smart Citations
“…Further, along with our mechanistic studies we observed a dramatic impact of the positive charges of the Mn porphyrin on the O 2 •− dismutation; the rate constants are more than two orders of magnitude higher when compared to the neutral or negatively charged porphyrins [3,4]. Thus, Mn III TE-2-PyP 5+ is 130-fold more potent SOD mimic than its singly charged Mn III Br 8 T-2-PyP + [3], and 400-fold more potent than its negatively charged analogue [Mn III Br 8 TSPP] 3− [4]. Charge distribution had also remarkable impact [2].…”
Section: Introductionsupporting
confidence: 61%
“…Synthesis of β-octabromo-meso-tetrakis(N-methylpyridinium-3-yl)porphyrinato-manganese (II) chloride, Mn II Br 8 TM-3-PyPCl 4 This fully β-brominated complex was prepared from H 2 TM-3-PyP 4+ in four steps. The first three steps were based on the synthetic protocol reported by Richards et al [30] In the third step, the Cu II Br 8 TM-3-PyP 4+ complex (45.6 mg, 0.0301 mmol) was demetallated by the slow addition of a concentrated sulfuric acid (6.0 mL, 111 mmol) while cooled to 10°C…”
Section: Electrochemistrymentioning
confidence: 99%
See 3 more Smart Citations